Nan Goldin: I’ll Be Your (Complex) Mirror - Richard PHELAN (E-REA)
When writing a “visual diary” through her photographs, American photographer Nan Goldin was less interested in the technical quality of the images she produced than in the narrative power achieved through their combination. Published in book form like The Ballad of Sexual Dependency and presented—as a slide show set to music, Goldin’s orchestrated sequences differ from the traditional photographic self-portrait presented as a unit for isolated contemplation. But, if the word “diary” is frequently used by the artist herself and by others to refer to her work, to what extent is the analogy or suggested kinship with verbal autobiography pertinent and in what way may it be said to actually inform her work?